2021
DOI: 10.1643/i2019318
|View full text |Cite
|
Sign up to set email alerts
|

Blackwater Diving: An Exciting Window Into the Planktonic Arena and Its Potential to Enhance the Quality of Larval Fish Collections

Abstract: Blackwater diving,'' or nighttime SCUBA diving in epipelagic environments, has become highly popular in recent years because lay participants encounter animals that are difficult and expensive to observe through other methods. These same observations can be priceless for researchers working with these species, so an interface between the scientific communities and recreational divers would be mutually beneficial. In this paper, we describe one such interface through the photography, collection, and DNA barcodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This method is indeed very promising and several rarely reported medusae species were encountered [see e.g. also Nonaka et al (2021) for a similar study on fish larvae].…”
Section: Species Identificationsmentioning
confidence: 99%
“…This method is indeed very promising and several rarely reported medusae species were encountered [see e.g. also Nonaka et al (2021) for a similar study on fish larvae].…”
Section: Species Identificationsmentioning
confidence: 99%
“…For example, these specimens include the associated recordings of anuran calls (Fig. 4) and videography and photography of specimens in situ made prior to collection that record behaviors (Nonaka et al, 2021). More generally, specimens can be viewed as including any aspect of the specimen that can be archived, curated, and used to advance the understanding of its biology, including data points related to the physical object.…”
Section: What Is a ''Specimen''?mentioning
confidence: 99%
“…More recently, it has also been suggested that the metabolic changes that occur during larval development in teleosts may be regulated by TH, as demonstrated in clownfish [14]. Of note in some cases, like groupers (elongated spines) [16][17][18] or carapids (vexillum appendage) [19], some changes occur very early on and are considered as temporary specialization of the pelagic larval stages, serving as anti-predator defense [20], flotation [21] or camouflage [22]. It is still unclear if these are late developmental processes occurring after hatching or early manifestations of metamorphosis.…”
Section: Introductionmentioning
confidence: 99%